The Neuropsychological Function of Older First-Time Child Exploitation Material Offenders: A Pilot Study - Rodriguez, Marcelo (International journal of offender therapy and comparative criminology, 2018)
Despite the growing incidence of child exploitation offences, there is little knowledge of the neuropsychological function of older child exploitation material offenders (CEMOs). Given that studies have reported that sex offenders demonstrate deficits attributed to frontal and temporal lobe function, the aim of this pilot study was to investigate the frontotemporal function of older first-time child exploitation material offenders (FTCEMOs). The neuropsychological performance of 11 older FTCEMOs was compared with 34 older historical sex offenders (HSOs) and 32 older nonsex offender (NSO) controls. Forty-five percent of FTCEMOs admitted to a pedophilic interest, which was significantly lower than those reported by HSOs. FTCEMOs provided significantly higher intellectual function scores than HSOs. Results revealed no evidence of mild or major neurocognitive disorder in FTCEMOs. Although the groups were not significantly different, compared with normative data, FTCEMOs reported a high incidence of impairment on a measure of decision making and on a measure of facial emotional recognition.